Introduksi Teknologi Pengolahan Pakan di Kecamatan Pattallassang Kabupaten Gowa Propinsi Sulawesi Selatan - Purwanti, Sri; Agustina, Laily; Nadir, Marhamah; Nohong, Budiman; Jamila, Jamila; Jamilah, Jamilah (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
The purpose of science and technology activities for the community is to provide skills to farmers groups inutilizing the potential of existing natural resources as an alternative to ducks, utilizing high-protein ammonia bran, andmaking herbs as additive feed. Specific targets to be achieved are the fulfillment of livestock nutrition needs, especiallyducks with resource utilization with the fulfillment of food needs. Not only use the feed without processing. Through thisactivity farmers and agricultural extension, workers are expected to synergize to learn to utilize available local food,raising public awareness to utilize local resources into the nutrient-rich feed. Method of implementation of activities to becarried out is the socialization of activities on farmer groups, training for members of farmer groups, how to make a feedwith some feed processing technology and assistance to farmers. Output target IbM program is an alternative ration forducks, ammonia bran as a source of protein, herbal medicine. The method used is PRA (Participatory Rural Appraisal) /RRA (Rapid Rural Appraisal). Learning methods, extension training, training, and visits (Laku), field school education(SL), demonstration plots, guidance and mentoring, learning by doing. The resulting results of the system. Breeders arenot familiar with feed processing technology and farmers have not utilized local feed as a constituent of rations. Thetechnology applied to the breeder group is to use herbal ingredients as a feed additive, making silage as a source ofprotein one source for duck livestock